2008
DOI: 10.1590/s1806-37132008001200004
|View full text |Cite
|
Sign up to set email alerts
|

Influência do dreno pleural sobre a dor, capacidade vital e teste de caminhada de seis minutos em pacientes submetidos à ressecção pulmonar

Abstract: The results of the present study suggest that the presence of a chest tube is a factor significantly associated with postoperative pain and functional limitation in patients submitted to pulmonary resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
2
10
0
2
Order By: Relevance
“…Several studies showed similar results to our study (21-23). However, some studies reported a lower sensitivity of about 20% to 50% (20, 21, 24).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several studies showed similar results to our study (21-23). However, some studies reported a lower sensitivity of about 20% to 50% (20, 21, 24).…”
Section: Discussionsupporting
confidence: 92%
“…In fact, the procedures used for bacilloscopy by such studies, were all rather indirect smear microscopy tests and the variety in their sensitivity may have been due to common laboratory errors. Lima et al compared smear microscopy with the LJ culture method and found a kappa coefficient of 0.62, which was almost the same as that found by our study (0.583) (23). …”
Section: Discussionsupporting
confidence: 90%
“…In the analysis on the analogue pain scale, there was no significant difference between the values, but they decreased after the operation and this may have been related to removal of the drains. The study by Lima et al 23 evaluated the influence of the thoracic drain on the reported pain and found that drain removal resulted in decreased analogue pain scores, which suggests that presence of a chest tube is an important factor associated with pain and functional limitations.…”
Section: Discussionmentioning
confidence: 99%
“…As in other studies [13][14][15][16] , the VC was measured by use of an analogue ventilometer (Ohmeda Respirometer ® , model RM 121, Japan). During this procedure, the patients sat down with their feet supported and nostrils occluded by a nose clip.…”
Section: Methodsmentioning
confidence: 99%